The quality of nursing care in dying children from the nurses’ point of view in Iran: A cross-sectional study - Fatemeh Ahmadi-Forg; Mohammad Hossein Sattari; Hadi Hasani (Heliyon)
Background: Nowadays, the quality of nursing care is one of the most essential factors in health services and patient care. The quality of end-of-life care is of high importance, especially in vulnerable groups such as children. In the final stages of life, the needs of patients and their companions, as well as stressful conditions cause avoidance of participation in treatment, and dissatisfaction of caregivers which can reduce the quality of patient care. The present study aimed to examine the quality of nursing care in children from the point of view of nurses in hospitals related to Birjand, Iran. Materials and methods: The present descriptive study was conducted on 350 nurses. The data collection tools used in this study were demographic questionnaire and Quality Patient Care Scale (QUALPAC). Results: A total of 270 completed questionnaires were entered into the statistical analysis. The average quality of nursing care score in dying children was 266.17 ± 27.79. Also, the results of the present study showed that the gender, age, marital status, and work experience of nurses have no significant effect on the quality of nursing care in dying children from the nurses’ viewpoint. Conclusion: The quality of nursing care of dying children from the point of view of nurses was satisfactory. Nurses reported that the physical dimension of nursing care had the highest quality and the psychosocial dimension had the lowest quality. Therefore, psychological support and follow-ups for improving social support for these clients are suggested to the nursing managers and healthcare administrators.